Pengaruh E-commerce Dan Pemahaman Sistem Informasi Akuntansi Dalam Pengambilan Keputusan Untuk Berwirausaha Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Islam Universitas Islam Negeri Sumatera Utara Medan - Haikal Fikri; Kusmilawaty Kusmilawaty; Yenni Samri Juliati Nasution (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2023)
This study aims to find out how understanding accounting information systems and e-commerce influences the decision to become an entrepreneur. Quantitative research is used in this type of research. Participants in this research are students who have studied accounting information systems. In this study, primary data was collected by distributing questionnaires directly to 100 respondents and processed with SPSS 20. The results showed that the decision to entrepreneurship was partially influenced by e-commerce, the decision to entrepreneurship was partially influenced by an understanding of accounting information systems, and the decision to Entrepreneurship is simultaneously influenced by e-commerce and understanding of accounting information systems.